Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Perceptions des professionnels de la santé quant aux besoins oncologiques pédiatriques offerts en français à domicile : étude descriptive qualitative - Chartrand, Julie; Jibb, Lindsay; Grandmont, Camille; Hardy-Bélanger, Élisabeth; Cheng, Sara; Balasa, Rebecca; Johnston, Donna (Revue canadienne de soins infirmers en oncologie, 2022)

The principle of minority protection and language rights in Canada: The secession reference’s legacy - Chouinard, Stéphanie (Journal of Parliamentary and Political Law, 2021)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Faire tomber les barrières linguistiques en santé : pour des soins et des services de santé de qualité, sécuritaires et équitables - Comité sénatorial permanent des langues officielles (Sénat du Canada / Senate of Canada, 2026)
Au Canada, les responsabilités en matière de santé et de langue sont partagées. Les attentes sont élevées à l’égard du gouvernement fédéral afin qu’il agisse comme chef de file pour protéger les droits linguistiques de la population canadienne en matière de santé. Dans le contexte où les différents paliers de gouvernement travaillent à bâtir un Canada plus fort, chaque Canadienne et Canadien devrait pouvoir bénéficier de services de santé dans la langue officielle de son choix. Dans ce rapport, le Comité sénatorial permanent des langues officielles présente les résultats de 18 mois d’audiences publiques ayant porté sur le thème de l’accès aux services de santé dans la langue de la minorité. Au total, ce sont 121 témoins et 36 soumissions écrites qui ont alimenté les 14 recommandations du Comité sénatorial. Celles-ci ont pour objectif de faire tomber les barrières linguistiques en santé. Ce rapport s’adresse à divers ministres fédéraux ainsi qu’à leurs partenaires en vue d’assurer des soins de qualité, sécuritaires et équitables. Il prône le respect du droit des utilisateurs du système de santé à recevoir des services dans une langue qu’ils comprennent et dans laquelle ils souhaitent être compris. De cette manière, les résultats en santé s’en trouveraient inévitablement améliorés. Le Comité sénatorial constate dans son rapport que les iniquités en santé ont un coût pour lequel les communautés de langue officielle en situation minoritaire payent trop souvent le prix. Le manque de planification sur l’ensemble du continuum de soins et de services de santé explique en partie ces piètres résultats. Pourtant, le gouvernement fédéral peut donner l’exemple afin d’offrir une gamme complète de services dans la langue officielle de son choix dans tous les milieux de soins et à toutes les étapes de la vie. Évidemment, la collaboration avec l’ensemble de ses partenaires demeure essentielle Note: Le rapport résume les témoignages entendus et les soumissions écrites reçues entre avril 2023 et novembre 2024, mais il ne tient pas compte de l’ensemble des développements survenus sur les scènes publique et politique depuis. Cela dit, les constats exposés dans ce rapport ainsi que les recommandations qui en découlent restent d’actualité.

Une question de respect et de sécurité : l’incidence des situations d’urgence sur les langues officielles - Commissariat aux langues officielles (Gouvernement du Canada, 2020)

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

50 ans de législation en matière de langues officielles au Canada : bilan et perspectives - Forgues, Éric; Donovan, Patrick; Labelle Eastaugh, Érik; O’Donnell, Lorraine (Minorités linguistiques et société / Linguistic Minorities and Society, 2021)
Les textes présentés dans ce numéro sont issus du colloque « 50 ans de mise en œuvre de la Loi sur les langues officielles : bilan et perspectives », qui s’est déroulé dans le cadre du 87e Congrès de l’Association francophone pour le savoir (Acfas) en 2019. Ce colloque nous a permis d’apprécier l’évolution de la question des langues officielles et du contexte politique dans lequel elle s’est posée au pays. Ce numéro présente des textes d’acteurs de premier plan sur la scène des langues officielles, tels que le Commissaire aux langues officielles, Raymond Théberge, l’ancien juge à la Cour suprême du Canada Michel Bastarache, l’avocate Marion Sandilands et les organismes porte-parole des CLOSM, soit la Fédération des communautés francophones et acadienne du Canada et le Quebec Community Groups Network

50 Years of Legislation Concerning Official Languages in Canada: Review and Prospects - Forgues, Éric; Donovan, Patrick; Labelle Eastaugh, Érik; O’Donnell, Lorraine (Linguistic Minorites and Society / Minorités linguistiques et société, 2021)
The articles presented in this issue stem from the symposium entitled “50 Years of Implementing the Official Languages Act: Review and Prospects”, which took place during the 87th congress of the Association francophone pour le savoir (Acfas) in 2019. This symposium was an occasion to take stock of the evolution of the official languages question within its Canadian political context. The issue features articles by key stakeholders on the official languages scene, such as the Commissioner of Official Languages, Raymond Théberge; former Supreme Court of Canada Justice, Michel Bastarache; lawyer Marion Sandilands; and the organizations that speak for OLMCs, namely the Fédération des communautés francophones et acadiennes du Canada and the Quebec Community Groups Network.

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)
Au début de la pandémie, un relâchement des obligations linguistiques dans les institutions publiques et les gouvernements a été observé (Chouinard & Normand, 2020). Ceci a pu avoir un impact sur les proches aidants et les bénéficiaires de soins en situation linguistique minoritaire. Notre équipe a voulu documenter le vécu de personnes proches aidantes en réalisant une étude à méthodologie mixte sur l’impact de la pandémie de la COVID-19 sur les personnes proches aidantes de personnes aînées et sur la relation aidant-aidé. Les résultats détaillés sont présentés dans l'article : Savard J. et al. (2026). Prolonged impact of the COVID-19 Pandemic... Nous avons choisi de synthétiser le vécu des proches aidants vivant en situation linguistique minoritaire par des récits inspirés des témoignages recueillies dans cette étude. Le récit suivant a été formulé à partir d'entretiens individuels auprès de quatre proches aidantes provenant de trois provinces canadiennes, dont la personne aînée recevant les soins demeurait dans un domicile privé.

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Institut de recherche Bruyère/Bruyère Research Institute, 2022)

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institute/Institut de recherche Bruyère, 2022)

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final présenté à Santé Canada - Léger (2020)
Ce rapport de recherche sur l’opinion publique présente les résultats d’un sondage Web et de groupes de discussion en ligne menés par Léger Marketing inc. pour le compte de Santé Canada. La recherche a été menée auprès de Canadiens vivant dans une situation où leur langue officielle est minoritaire. Santé Canada, par l’entremise du BACLO, appuie la mise en œuvre d’activités visant à favoriser le dynamisme et le développement des CLOSM ainsi que la pleine reconnaissance et l’usage du français et de l’anglais dans la société canadienne. L’un des principaux objectifs du BACLO est d’améliorer l’accès aux services de soins de santé pour les CLOSM dans la langue officielle de leur choix. Pour documenter cette question, Santé Canada a entrepris un projet de collecte de données quantitatives et qualitatives afin de mieux comprendre les obstacles auxquels les CLOSM peuvent être confrontés pour accéder aux services de santé dans la langue officielle de leur choix, ainsi que les facteurs qui facilitent cet accès. Les résultats de cette étude témoigneront de l’expérience vécue par les CLOSM en matière d’accès aux services de soins de santé dans la langue officielle de leur choix et aideront à identifier les principales lacunes ainsi que les éléments facilitants

Perceptions des communautés de langue officielle en situation minoritaire: accès aux services de santé dans la langue officielle de son choix - Sommaire exécutif présenté à Santé Canada - Leger (2020)
Ce rapport de recherche sur l’opinion publique présente les résultats d’un sondage Web et de groupes de discussion en ligne menés par Léger Marketing inc. pour le compte de Santé Canada. La recherche a été menée auprès de Canadiens vivant dans une situation où leur langue officielle est minoritaire. Santé Canada, par l’entremise du BACLO, appuie la mise en œuvre d’activités visant à favoriser le dynamisme et le développement des CLOSM ainsi que la pleine reconnaissance et l’usage du français et de l’anglais dans la société canadienne. L’un des principaux objectifs du BACLO est d’améliorer l’accès aux services de soins de santé pour les CLOSM dans la langue officielle de leur choix. Pour documenter cette question, Santé Canada a entrepris un projet de collecte de données quantitatives et qualitatives afin de mieux comprendre les obstacles auxquels les CLOSM peuvent être confrontés pour accéder aux services de santé dans la langue officielle de leur choix, ainsi que les facteurs qui facilitent cet accès. Les résultats de cette étude témoigneront de l’expérience vécue par les CLOSM en matière d’accès aux services de soins de santé dans la langue officielle de leur choix et aideront à identifier les principales lacunes ainsi que les éléments facilitants

Perceptions from official language minority communities : Access to health services in the official language of choice 2020. Executive summary submitted to Health Canada. - Léger (2020)
This public opinion research report presents the results of a web survey and online focus group discussions conducted by Leger Marketing Inc. on behalf of Health Canada. The research was conducted with Canadians living in an official language minority situation. Health Canada, through the OLCDB, supports the implementation of activities to enhance the vitality and developments of OLMCs as well as the full recognition and use of English and French in Canadian society. One of the OLCDB’s key objectives is to improve access to health care services for OLMCs in the official language of their choice. To document this issue, Health Canada undertook a quantitative and qualitative data collection project to better understand the barriers that OLMCs may encounter in accessing health services in the official language of their choice, as well as enablers that facilitate this access. The results of this study will document the lived experience of OLMCs in accessing health care services in their official language of choice and will help identify key gaps and enablers.

Perceptions from official language minority communities : Access to health services in the official language of choice 2020. Final report submitted to Health Canada. - Léger (2020)
This public opinion research report presents the results of a web survey and online focus group discussions conducted by Leger Marketing Inc. on behalf of Health Canada. The research was conducted with Canadians living in an official language minority situation. Health Canada, through the OLCDB, supports the implementation of activities to enhance the vitality and developments of OLMCs as well as the full recognition and use of English and French in Canadian society. One of the OLCDB’s key objectives is to improve access to health care services for OLMCs in the official language of their choice. To document this issue, Health Canada undertook a quantitative and qualitative data collection project to better understand the barriers that OLMCs may encounter in accessing health services in the official language of their choice, as well as enablers that facilitate this access. The results of this study will document the lived experience of OLMCs in accessing health care services in their official language of choice and will help identify key gaps and enablers.

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

The revised patient perception of patient-centeredness questionnaire: Exploring the factor structure in French-speaking patients with multimorbidity - Nguyen, Tu Ngoc; Ngangue, Patrice Alain; Ryan, Bridget. L.; Stewart, Moira; Brown, Judith. B.; Bouhali, Tarek; Fortin, Martin (Health Expectations, 2020)
Background The Patient Perception of Patient-Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC-R) in French-speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient-Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health-care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC-R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC-R showed very good internal consistency, with three factors: Patient-Centered Clinical Method (PCCM) Component 1-Exploring the health, disease and illness experience + PCCM Component 4-Enhancing the patient–clinician relationship (Factor 1); PCCM Component 2-Understanding the whole person (Factor 2); and PCCM Component 3-Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC-R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient-centeredness.

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Les langues officielles et les travailleurs de la santé au Canada: Un portrait. - Ouellet-Léveillé, Bertrand; St-Amant, Gabriel (Statistique Canada, 2025)

Official languages and health care workers in Canada: A portrait. - Ouellet-Léveillé, Bertrand; St-Amant, Gabriel (Statistics Canada, 2025)

Connaissance et utilisation de la langue officielle minoritaire au travail par les travailleurs de la santé, 2001 à 2016 - Paez Silva, Alejandro. A.; Cornelissen, Louis (Statistique Canada, 2021)

Knowledge and use of the Official Minority Language at work by healthcare workers, 2001 to 2016 - Paez Silva, Alejandro. A.; Cornelissen, Louis (Statistics Canada, 2021)

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Ce rapport présente les principaux résultats de l’Enquête sur la population de langue officielle en situation minoritaire (EPLOSM) de 2022. Il brosse un portrait d’ensemble de la situation des populations de langue anglaise au Québec et de langue française dans les autres provinces et les capitales des territoires du Canada. Cette enquête a été menée afin de mieux comprendre la situation des personnes de langue officielle en situation minoritaire en ce qui concerne certains sujets et enjeux actuels, comme la scolarité, les services à la petite enfance, l’accès à d’autres services dans la langue officielle minoritaire et leur utilisation, ainsi que les pratiques linguistiques à la maison, au travail et dans l’espace public. L’enquête, qui représente une collaboration entre Statistique Canada et Patrimoine canadien, vise à soutenir les utilisateurs de données sur les communautés de langue officielle en situation minoritaire. L’Enquête sur la population de langue officielle en situation minoritaire de 2022 est une enquête postcensitaire, c’est‐à‐dire que son échantillon provient du Recensement de la population de 2021. La population de langue officielle en situation minoritaire désigne la population de langue anglaise au Québec et la population de langue française au Canada hors du Québec. L’enquête a été menée dans les 10 provinces canadiennes du 16 mai au 16 décembre 2022, ainsi que dans les capitales des trois territoires canadiens du 22 août au 16 décembre 2022. Au total, près de 30 000 personnes y ont répondu. L’échantillon des adultes comprend 13 892 répondants, alors que l’échantillon des enfants compte 16 066 enfants pour lesquels un parent ou un tuteur a répondu à certaines questions portant sur leur enfant et à d’autres portant sur eux‐mêmes.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
The 2022 Survey on the Official Language Minority Population (SOLMP) was conducted to shed light on different aspects of the situation of the English‐speaking population in Quebec and the French‐speaking populations in Canada’s other provinces and the territory capitals. This report presents the key findings from the 2022 Survey on the Official Language Minority Population (SOLMP). It provides an overview of the situation of English‐speaking populations in Quebec and French‐speaking populations in Canada’s other provinces and the territory capitals. This survey was conducted to better understand the situation of official language minorities with respect to certain topics and current issues, such as education, early childhood services, access to and use of other services in the minority official language, as well as language practices at home, at work and in the public sphere. The survey, which represents a collaboration between Statistics Canada and Canadian Heritage, aims to support users of data on official language minority communities.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.

Breaking Down Language Barriers in Health Care: For Equitable, Safe and Quality Health Care and Health Services - Standing Senate Committee on Official Languages (Sénat du Canada / Senate of Canada, 2026)
In Canada, health and language are both areas of shared jurisdiction. People have high expectations that the federal government will take on a leadership role in protecting thelanguag e rights of the Canadian population when it comes to health care. In a context where the various levels of government are working to build a stronger Canada, every Canadian should be able to receive health services in the official language of their choice. In this report, the Standing Senate Committee on Official Languages outlines the findings resulting from a series of public hearings held over 18 months on the theme of access to health care services in the minority language. In total, 121 witnesses and 36 written submissions led the Senate Committee to make 14 recommendations. The recommendations focus on reducing language barriers in health care. This report is directed at various federal ministers and partners in an effort to ensure equitable, safe and quality care. It advocates for the right of health system users to receive services in a language they understand and in which they would like to be understood. Accordingly, this approach would lead to improved health outcomes. The Senate Committee notes that health inequities come at a cost, and official language minority communities are often the ones paying the price. The lack of planning across the health care services continuum is partly responsible for these poor outcomes. However, the federal government could set the standard of offering a full range of services in the official language of choice in all care settings and at all stages of life. Of course, this would require continued collaboration with all its partners. Note: This report summarizes the evidence heard and the written submissions received between April 2023 and November 2024, but it does not address all the developments that have taken place in the public and political spheres since then. However, the findings and recommendations in this report are still relevant in the current context.

Language indicators over time: Interactive Dashboard - Statistics Canada (Statistics Canada, 2025)

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

Diversité linguistique au Canada, 2021 : tableau de bord interactif - Statistique Canada (2021)

How poverty rates differed by language in Quebec, New Brunswick and Ontario in 2021 - Statistique Canada (2026)

Indicateurs linguistiques au fil du temps : tableau de bord interactif - Statistique Canada (Statistique Canada, 2025)

Language diversity in Canada, 2021: Interactive dashboard. - Statistique Canada (2026)

Poverty rate of the bilingual population in Quebec, New Brunswick and Ontario in 2021 - Statistique Canada (2026)

Taux de pauvreté au sein de la population bilingue du Québec, du Nouveau-Brunswick et de l’Ontario, 2021 - Statistique Canada (2021)

Variations dans les taux de pauvreté selon la langue au Québec, au Nouveau-Brunswick et en Ontario - Statistique Canada (2021)

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.

Do nurses use discourse markers differently when using their second language as opposed to their first while interviewing patients? - Yeji, Han; Segalowitz, Norman; Khalil, Laura; Kehayia, Eva; Turner, Carolyn; Gatbonton, Elisabeth (The Canadian Modern Language Review, 2020)
Les auteurs se demandent si l’utilisation de marqueurs discursifs change, dans les interactions des infirmières avec les patients, en fonction de l’usage qu’elles font de leur langue maternelle (L1) ou de leur langue seconde (L2). Les marqueurs sont analysés à titre de marqueurs de maintien du tour de parole, indiquant la « prise en compte » et de marqueurs de transition dans le discours, indiquant un changement de sujet ou de locuteur dans la conversation. Ces deux catégories de marqueurs diffèrent sur le plan du degré de gestion du discours et du contrôle interactionnel. Seize infirmières mènent auprès d’un patient de L1 anglaise et d’un patient de L1 française un entretien visant l’évaluation de la douleur, entretien dans lequel les infirmières utilisent leur propre L1 dans un cas et leur propre L2, moins bien maîtrisée, dans l’autre. Les résultats de l’étude ne permettent pas de confirmer la première hypothèse, selon laquelle les infirmières devraient normalement utiliser les marqueurs discursifs plus fréquemment en L1 qu’en L2. Ils confirment toutefois la seconde hypothèse, selon laquelle les infirmières devraient utiliser les marqueurs de changement de sujet moins fréquemment en L2 qu’en L1, comparativement à leur usage (de base) des marqueurs de maintien du tour de parole. Les constatations des auteurs, en particulier l’attestation de la seconde hypothèse, pourraient avoir des répercussions sur le développement de la formation en L2 des professionnels de la santé.